Draft Annual Plan 1988-89 Government of Meghalaya - Planning Commission (Planning Commission, 1988)
Meghalaya covers an area of 22,500 square kilometres approximately which is 0.70 per cent of the total area of India. Its population in 1981 was 13.36 lakhs constituting 0.19 per cent of India's total papulation. In terms of population size, Meghalaya is one of the smallest in the country. The population of Meghalaya has increased from 10.12 lakhs in 1971 to 13.36 lakhs in 1981. the growth rale for the decade was 32.08 per cent as against the all-India rale of 27.21 per cent. The density of population in the State in 1981 was 80 persons-per square kilometre compared to 15 persons in 1971.
Planning Department Government of Meghalaya